Techonology management capability profiles as obtained from the analysis and modeling of integrated technology management processes: The case of automotive suppliers industry and supermarkets in Turkey - Yüksel, Birol (My University, 2000)
Technology is widely recognised to be essential to competitiveness in dynamic social and economic environments of 1990s and it has become a key resource for firms to create and sustain competitive strengths. Therefore, firms should develop their knowledge and skills in managing technology. The management of technology is actually planning, development and implementation of technological capabilities to integrate technology strategy with business strategy. This integration requires all functions of firms such as marketing, sales, R&D, human resources, finance, investment, production to work together to accomplish strategic and operational objectives. The firms that want to implement an integrated technology management approach as a part of their business strategy must have sufficient technological and managerial capabilities. These capabilities are embodied in three levels of management (operational, strategic and normative) in relation with their structures, behaviors and objectives. At that point, the challenge is the development of a model that determines the sufficiency of technology management capabilities at each level of management. Such a model will allow us to diagnose the actual source of deficiency in management to implement integrated technology management strategy. The next stage is the implementation of the model called as Technology Processes Management Capabilities Assessment Model. The model was applied firstly in Turkish automotive suppliers industry. The results of the model gave a good opportunity for identification of strategic behaviors of sector's firms. The flexibility of any model is an important indicator for its effectiveness. Therefore, the model was also implemented in supermarkets industry with slight modifications to see its flexibility and provide a conceptualization of technology management in service industries. In

, the study is an application of a wide range of theoretical concepts of integrated technology management in a real business environment and it is intended to constitute a good basis for future studies in the area of integrated technology management. ÖZET Teknoloji, 1990'lı yılların dinamik sosyal ve ekonomik ortamlarında rekabetin gereği olarak görülmektedir. Teknoloji, rekabet gücü yaratmanın ve bu gücü muhafaza etmenin en önemli kaynağı olmuştur. Bundan dolayı, şirketler teknolojiyi yönetmeye yönelik bilgi ve kabiliyetler geliştirmek durumundadırlar. Teknoloji yönetimi aslında teknoloji stratejisi ile iş stratejisini entegre etmek için teknolojik kabiliyetlerin planlanması, geliştirilmesi ve uygulanmasıdır. Bu entegrasyon, firmanın pazarlama, satış, ar-ge, insan kaynakları, mali işler, yatırım ve üretim fonksiyonlarının hepsinin operasyonel ve stratejik hedefleri başarmak üzere birlikte çalışmalarını gerektirir. Entegre teknoloji yönetimi yaklaşımını, iş stratejilerinin bir parçası olarak uygulamak isteyen firmalar, yeterli yönetsel ve teknolojik kabiliyetlere sahip olmak zorundadırlar. Bu kabiliyetler, operasyonel, stratejik ve üst düzey olarak adlandırılan ve kendilerine özgü, davranışları, yapıları ve amaçları olan yönetim kademelerinde bulunurlar. Bu noktada, üstesinden gelinmesi gereken şey, her bir yönetim kademesinin teknoloji yönetimi kabiliyetlerinin yeterliliğinin tespit edilmesi sağlayacak bir modelin geliştirilmesidir. Bu şekilde tasarlanacak bir model, entegre teknoloji yönetimi stratejisini uygulamakta yetersizlik gösteren yönetim kademesinin teşhis edilmesine olanak tanıyacaktır. Bundan sonraki aşama ise Teknoloji Süreçlerini Yönetme Kabiliyetlerini İrdeleme Modeli olarak adlandırılan modelin uygulamaya konmasıdır. Model öncelikle Türkiye otomotiv yan sanayi sektöründe uygulanmıştır. Modelin ürettiği sonuçlar, bu sektörde yer alan firmaların stratejik davranışlarının tanımlanması için iyi bir olanak sağlamıştır. Esneklik, bir modelin etkinliğinin en önemli göstergesidir. Teknoloji Süreçlerini Yönetme Kabiliyetlerini İrdeleme Modeli, gerek esnekliği görmek ve gerekse teknoloji yönetiminin hizmet sektöründe kavranmasını sağlamak için süpermarket sektöründe de ufak değişikliklerle uygulanmıştır. Özet olarak, bu çalışma geniş bir kapsamı olan entegre teknoloji yönetiminin teorik kavramlarının bir uygulamasıdır ve gelecekte entegre teknoloji yönetimi alanında yapılacak çalışmalar için iyi bir temel oluşturma niyeti gütmektedir.
Keywords: OTOMOTIV ENDÜSTRİSİ-TEKNOLOJİ; SUPERMARKET ENDÜSTRİSİ-TEKNOLOJİ